Patterns and Trends in Grade Retention Rates in the United States, 1995–2010. (December 2014) - Warren, John Robert; Hoffman, Emily; Andrew, Megan
Although grade retention may be consequential for a number of important educational and socioeconomic outcomes, we know surprisingly little about the actual rate at which students are made to repeat grades. We build on Hauser, Frederick, and Andrew's 2007 measure of grade retention using data from the 1995 through 2010 Current Population Surveys. We make technical improvements to their measure, provide more recent estimates, and validate the measure against external criteria. Our measure describes large disparities in grade retention rates by sex, race/ethnicity, geographic locale, and students' socioeconomic circumstances. However, both absolute retention rates and disparities in retention rates have declined markedly since 2005. We conclude by describing how our measures might be used to model the impact of economic and policy contexts on grade retention rates.